Impact of evidence-based nursing interventions on psychological status and myocardial injury in patients with myocardial infarction following percutaneous coronary intervention for reperfusion injury - Li, Ni; Chen, Xi (Frontiers in Physiology, 2025)
ObjectivePercutaneous coronary intervention for myocardial infarction can cause reperfusion injury with both physical and psychological impacts on patients. This study aims to assess how evidence-based nursing affects psychological state and myocardial injury in reperfusion injury in patients with myocardial infarction following percutaneous coronary intervention.MethodNinety patients with myocardial infarction who underwent percutaneous coronary intervention and were confirmed to have postoperative reperfusion injury were randomly divided into a control group that received conventional care or an intervention group that received evidence-based nursing intervention. The levels of cardiac function indicators (left ventricular ejection fraction and left ventricular end-diastolic diameter), myocardial injury markers (N-terminal pro-b-type natriuretic peptide and cardiac troponin I), psychological status (Self-Rating Anxiety Scale and Self-Rating Depression Scale scores), the incidence of complications, mortality rate, and satisfaction with nursing care were compared before and after the intervention.ResultsCompared to pre-intervention, after the intervention, both groups showed reductions in left ventricular end-diastolic diameter, N-terminal pro-b-type natriuretic peptide, cardiac troponin I levels, Self-Rating Anxiety Scale and Self-Rating Depression Scale scores, with an increase in left ventricular ejection fraction. The intervention group demonstrated superior outcomes in all these metrics compared to the control group, with lower rates of complications and mortality, and higher satisfaction levels.ConclusionImplementing evidence-based nursing in patients with myocardial infarction undergoing percutaneous coronary intervention for reperfusion injury can improve cardiac function, alleviate myocardial injury and psychological status, reduce the incidence of complications, and enhance patient satisfaction.